Analisis Faktor Risiko Maternal terhadap Keluarga Berisiko Stunting: Studi di Kabupaten Jember, Jawa Timur, Indonesia - Dr. Elok Permatasari, M.Kes.; Leersia Yusi Ratnawati; Ni'mal Baroya; Globila Nurika; Farida Wahyu Ningtyias; Andrei Ramani (Universitas Airlangga, 2022)
Background. In 2021, stunting in Indonesia remains high at 24.4%. Indonesian government has a target to decrease stunting prevalence become 14% in 2024. Jember is one of district in East Java with high stunting prevalence 23,4%. First thousand days of life influenced stunting, and maternal risk factor is one of determinants of stunting. In Indonesia was known as 4T, which is Too young, Too old, Too closed and Too much. Objectives. To analyze Maternal Risk Factor (4T) in families at risk of stunting in Jember district, East Java, Indonesia. Method. This research was ecological study by using secondary data with unit of analysis were 286344 families with stunting risk in Jember district. Source data collection using PK21 (Family Data base 2021) and child monitoring status 2019-2021. Data was analyzed by pearson and spearman correlation. Result. Based on Family data base 2021 in Jember showed that there were 84.19% family at risk of stunting. Maternal risk factor (4T) showed: Too young (age of wife < 19 years) 1.18%; Too old (age of wife > 35 years) 52.50%; too close (birth spacing < 2 years) 1.34%; too much (number of birth > 3) 18.03%. And there were corellation between maternal risk factor too young (0,003), too old (0,000), too close (0,000) and too much (0,000) with family at stunting risk. Conclusion. Stunting in Jember remains high and need prevention by reducing maternal risk factor including: too young, too old, too close, and too much. Keywords: Stunting, Maternal Risk Factor, 4T